TINJAUAN BIOMOLEKULAR PATOFISIOLOGI DAN PENEGAKAN DIAGNOSIS - Juwita; Hidayaturrahmi; Adista, Ansari; Khairunnisa (Jurnal Sinaps, 2023)
Cancer is characterized by the uncontrolled growth and spreading of abnormal cells. Cancer-induced bone pain (CIBP) is a significant problem affecting the majority of cancer patients, especially those suffering from metastatic disease due to cancer. The pathogenesis of CIBP involves tumor cells, bone cells, inflammatory microenvironment, and neural tissue. RNA noncoding miR-708-5p/CXCL13 has an important role in enhancement development of bone cancer pain through the initiation of neuroinflammation and hyperalgesia. Early recognition of bone pain in cancer and establishing a diagnosis are essential for timely intervention to relieve pain, prevent complications such as bone fractures, and improve the patient's quality of life. Management of bone pain in cancer patients is very complex and requires a multidisciplinary approach.